Pre-sowing magnetic treatment of tomato seeds: effects on the growth and yield of plants cultivated late in the season - De Souza, A.=700 1 D. Garcia, L.S.; Licea, L.; Porras, E.
(Es, En)
ilus., 37 ref.
Keywords: LYCOPERSICON ESCULENTUM; ESTIMULANTES DE CRECIMIENTO VEGETATIVO; SEMILLAS; CAMPO MAGNETICO; RENDIMIENTO; ESPAÑA; EPOCA TARDIA